Analisis Pemberian Pembiayaan Akad Mudharabah Di Bank Syariah Berdasarkan Fatwa Dsn - Dina Ofera; Ida Royani Ritonga (AGHNIYA : Jurnal Ekonomi Islam, 2019)
In Islamic financial institutions, financing has two agreements or agreements that are often carried out, namely murabahah and mudharabah. In the provision of financing using mudharabah contracts, usually the customers only have the ability, while the bank has capital that will be managed by the customer, with the provisions for profit sharing. For this reason, the research aims to look at the application of financing using mudharabah contract at bank muamalat.The approach of this research is a descriptive research approach, namely research that seeks to tell the problems that exist, by presenting, analyzing and interpreting the results of research. Technical data collection is done through interviews. PT. Bank Muamalat Medan City Hall Branch Office, has been implemented in accordance with DSN No. fatwa. 07 / DSN-MUI / IV / 2000, which can be seen from the contents of the contract agreement at PT. Bank Muamalat, related to profit sharing, provision of funds, type of business, dispute resolution, consent and qabul. Mudharabah is a system where the owner of a fund provides all funds for a business to someone who is responsible for carrying out the business and acting as mudarib.